Scoring system for prediction of metastatic spine tumor prognosis - Tokuhashi, Yasuaki (Baishideng Publishing Group Inc, 2014)
Assessing the prognosis before treatment for metastatic spine tumor is extremely important in therapy selection. Therefore, we review some prognostic scoring systems and their outcomes. Articles with combinations of two keywords among “metastatic spine tumor” and “prognosis”, “score”, “scoring system”, “predicting”, or “life expectancy” were searched for in PubMed. As a result, 236 articles were extracted. Those referring to representative scoring systems about predicting the survival of patients with metastatic spine tumors were used. The significance and limits of these scoring systems, and the future perspectives were described. Tokuhashi score, Tomita score, Baur score, Linden score, Rades score, and Katagiri score were introduced. They are all scoring systems prepared by combining factors that affect prognosis. The primary site of cancer and visceral metastasis were common factors in all of these scoring systems. Other factors selected to influence the prognosis varied. They were useful to roughly predict the survival period, such as, “more than one year or not” or “more than six months or not”. In particular, they were utilized for decision-making about operative indications and avoidance of excessive medical treatment. Because the function depended on the survival period in the patients with metastatic spine tumor, it was also utilized in assessing functional prognosis. However, no scoring system had more than 90% consistency between the predicted and actual survival periods. Future perspectives should adopt more oncological viewpoints with adjustment of the process of treatment for metastatic spine tumor.